Symptomatic first-degree atrioventricular block in a young woman after taking a fat burner supplement - Abdelmageed, Renda E. M.; Xiao, H.B. (International Journal of Health Sciences, 2017)
A 22-year-old woman collapsed at home and was brought to the accident and emergency department. History revealed that she was fit and taken T5 capsule the night before the collapse. There was no history of similar collapses or seizure. Examination revealed blood pressure (BP) of 104/69 mmHg and a heart rate (HR) of 70 bpm. Chest, cardiovascular, and neurology examination were unremarkable. However, on standing, her HR increased to 120 bpm, and her BP dropped to 62/40 mmHg. Blood Na, K, Ca, Mg, phosphate, creatinine, complete blood count, T4 cortisol, and thyroid-stimulating hormone (TSH) were normal. The electrocardiogram (ECG) on the ambulance revealed sinus rhythm with normal morphology but a significant first-degree atrioventricular block with a PR interval of 280-300 ms. The patient was treated for orthostatic hypotension with intravenous fluids. Her symptoms gradually improved. The repeat ECG taken 24 h after admission showed reduced PR interval to 230ms. The patient was followed up in the clinic after 1 week with normal ECG with a PR interval of 200 ms and a normal echocardiogram. The findings are discussed.